A Novel Adult Murine Model of Typical Enteroaggregative Escherichia coli Infection Reveals Microbiota Dysbiosis, Mucus Secretion, and AAF/II-Mediated Expression and Localization of β-Catenin and Expression of MUC1 in Ileum - Moran-Garcia, Nadia; Lopez-Saucedo, Catalina; Becerra, Adriana; Meza-Segura, Mario; Hernandez-Cazares, Felipe; Guerrero-Baez, Jair; Galindo-Gómez, Silvia; Tsutsumi, Víctor; Schnoor, Michael; Méndez-Tenorio, Alfonso; Nataro, James P.; Estrada-Garcia, Teresa (Frontiers in Cellular and Infection Microbiology, 2022)
Typical enteroaggregative Escherichia coli (tEAEC) is a diarrheagenic E. coli pathotype associated with pediatric and traveler’s diarrhea. Even without diarrhea, EAEC infections in children also lead to increased gut inflammation and growth shortfalls. EAEC strain’s defining phenotype is the aggregative adherence pattern on epithelial cells attributable to the aggregative adherence fimbriae (AAF). EAEC only causes diarrhea in humans; therefore, not much is known of the exact intestinal region of infection and damage or its interactions with intestinal enterocytes in vivo and in situ. This study aimed to develop a new tEAEC mouse model of infection, characterize the microbiota of infected mice, and evaluate in situ the expression of host adherence and surface molecules triggering EAEC infection and the role of the EAEC AAF-II in adherence. Six-week-old C57BL/6 mice, without previous antibiotic treatment, were orally challenged with EAEC 042 strain or EAEC 042 AAF-II mutant (ΔAAF/II) strain, or DAEC-MXR strain (diffusely adherent E. coli clinical isolate), and with saline solution (control group). Paraffin sections of the colon and ileum were stained with H&E and periodic acid-Schiff. ZO-1, β-catenin, MUC1, and bacteria were analyzed by immunofluorescence. EAEC-infected mice, in comparison with DAEC-MXR-infected and control mice, significantly lost weight during the first 3 days. After 7 days post-infection, mucus production was increased in the colon and ileum, ZO-1 localization remained unaltered, and morphological alterations were more pronounced in the ileum since increased expression and apical localization of β-catenin in ileal enterocytes were observed. EAEC-infected mice developed dysbiosis 21 days post-infection. At 4 days post-infection, EAEC strain 042 formed a biofilm on ileal villi and increased the expression and apical localization of β-catenin in ileal enterocytes; these effects were not seen in animals infected with the 042 ΔAAF/II strain. At 3 days post-infection, MUC1 expression on ileal enterocytes was mainly detectable among infected mice and colocalized with 042 strains on the enterocyte surface. We developed a novel mouse model of EAEC infection, which mimics human infection, not an illness, revealing that EAEC 042 exerts its pathogenic effects in the mouse ileum and causes dysbiosis. This model is a unique tool to unveil early molecular mechanisms of EAEC infection in vivo and in situ.